APPOINTMENT APPLICATION AT CLASS I NON-TPI BOGOR IMMIGRATION OFFICE - P. Assiroj; G.B Hertantyo; , K.Y Sugiyanto (Polteknik Imigrasi, 2022)
Manual appointments for immigration services are still used by Bogor Immigration Office. It is undeniable that the manual system has obstacles in its implementation such as not having a personal data recap of its visiting guests and the difficulty regarding the appointment registration mechanism. This study aims to determine the appointment mechanism at Bogor Immigration Office and provide a design application for an appointment. The research was conducted to overcome problems that occur in the application of the appointment mechanism and provide innovation in the form of a website-based appointment application. This design was carried out using the System Development Life Cycle (SDLC) method with the waterfall model. The results of this study are in the form of a website-based appointment application which can later be applied at the Bogor Immigration Office.